The Effect of Employee Engagement and Work Happiness on Employee Satisfaction - dewy cahyani; Rahmat Sabuhari; Zulaika Husen (TALENTA Publisher, Universitas Sumatera Utara, 2024)
This research was conducted with the aim of knowing and analyzing the effect of Employee Engagement and Work Happiness on Employee Satisfaction . Research data collection used questionnaires which were distributed to 55 respondents who worked as employees of the Regional Research and Development Agency for North Maluku Province. The model testing technique uses multiple linear regression. The analytical test tool uses SPSS version 25. The results of this study indicate that: (1) Employee engagement has a positive and significant effect on Employee Satisfaction. (2) Work happiness has a significant positive effect on employee satisfaction, (3) Employee engagement, work happiness both have a simultaneous and significant effect on employee satisfaction.